Fabrication of highly homogeneous surface-enhanced Raman scattering substrates using Ag ion implantation. (11th May 2016) - Li, Wenqing; Xiao, Xiangheng; Dai, Zhigao; Wu, Wei; Cheng, Li; Mei, Fei; Zhang, Xingang; Jiang, Changzhong
Abstract: In recent times, surface-enhanced Raman scattering (SERS) has attracted attention for its excellent potential application in chemical and biological detection. In this work, we demonstrate that a highly homogeneous SERS substrate can be realized by Ag ion implantation and the subsequent annealing process. Both the implantation and annealing parameters have been optimized for a high sensitivity SERS substrate. The SERS measurement indicates that a sample implanted by 20 kV Ag ions with a dosage of 3 × 10 16 ions cm −2 exhibits the highest SERS activity. In addition, the SERS activity of the Ag-implanted substrates depends highly on the annealing temperature and time. Since none of the fabrication processes contain chemical reactions, our substrate is a clean system without any chemical residues.